ANALISIS HARGA INTERNASIONAL, NILAI TUKAR, DAN KONSUMSI KAKO AMERIKA TERHADAP DAYA SAING EKSPOR KAKAO INDONESIA - Hatta Buana Sandry; Nazaruddin Malik (Program Studi Ekonomi Pembangunan, 2017)
This study aims to examine the export competitiveness of Indonesian cocoa and its influential factors during 1995 – 2015. The data analysis was carried out by using Time Series data published by the Central Bureau of Statistics (BPS), UN Comtrade, Cocoa World, Department of Agriculture, and Mundi Index. The method used in this study was RCA and PAM. The result of RCA analysis shows that the export competitiveness of Indonesian cocoa is considered good since the average export of cocoa was 1.25 during 1995 – 2015. Therefore, referring to this, Indonesian has shown a great deal of export competitiveness of cocoa and, thus, has a chance in cocoa industry. Meanwhile, the result of PAM analysis indicates that both International price and cocoa consumption in the United States have an impact on export competitiveness of Indonesian cocoa. Keywords: cocoa, cocoa consumption in America, competitiveness, export, International price